Time in the United States and diabetes among Mexican immigrant women: The moderating role of culture - Courtney Andrews; Kathryn S. Oths; William W. Dressler (Elsevier, 2022)
Mexican immigrants in the U.S. show high incidence of type 2 diabetes, and increased risk is associated with longer duration of residency. This study considers the impact of culture over time for Mexican immigrant women in a southern U.S. city. Using cultural consensus analysis to empirically derive the substance and structure of a cultural model for la buena vida (the good life) among Mexican immigrant women in Birmingham, Alabama, we assess the extent to which respondents are aligned with the model in their everyday lives. This measure of 'cultural consonance' is explored as a moderating variable between length of time living in the U.S. and level of Hemoglobin A1c. Results demonstrate that for those with more time in the U.S., those with lower consonance are more likely to have diabetes, while those who are more aligned with la buena vida are at lower risk.